Easy baking - Clark, Pamela (Sydney, N.S.W Australian Women's Weekly ; Northampton : Australian Consolidated [distributor], 2009)
We all love cakes, biscuits, slices and after-dinner treats, but we've run out of time to make them. And home-made is almost always better than store-bought. This book shows you how to can fill the cake tin even when you have limited time
2
NEW
Keywords: Baking